State of knowledge of the Mexican agouti (Dasyprocta mexicana): an understudied endemic mammal in Mexico: Conservation of D. mexicana - Rodas-Trejo, Jenner (Therya Notes, 2026)
Dasyprocta mexicana is a rodent species endemic to Mexico, currently classified as Critically Endangered by the IUCN but absent from Mexican environmental legislation. Its distribution includes the states of Veracruz, Oaxaca, Chiapas, and Tabasco, and it has been introduced to Cuba. The species is characterized as a diurnal frugivore-granivore, playing a key ecological role as a seed disperser. A systematic review of 42 scientific articles was conducted to document the current state of knowledge regarding the distribution, ecology, and conservation of the species. Presence of D. mexicana was documented in 17 localities, mainly within protected natural areas, with variable abundances. Results indicate a preference for well-preserved forests, although some studies report a degree of adaptability to disturbed habitats. The species faces critical threats including deforestation, habitat fragmentation, and subsistence hunting, having lost over one third of its natural habitat. Despite increased research efforts in the past decade, significant knowledge gaps remain. The discrepancy between its critical global status and national lack of protection highlights the urgent need to revise conservation policies and implement long-term monitoring and research programs to ensure its survival.